Value of Anterior Band of the Inferior Glenohumeral Ligament Area as a Morphological Parameter of Adhesive Capsulitis - Yun-Sic Bang; Junbeom Park; Sun Young Lee; Jiyeon Park; Sukhee Park; Young Joo; Young Uk Kim; Yoon Kyung Lee (Pain Research and Management)
Objective. Thickened inferior glenohumeral ligament (IGHL) is considered as one of the major morphological parameters of adhesive capsulitis (AC). Previous studies reported that the anterior band of inferior glenohumeral ligament thickness (aIGHLT) is correlated with shoulder capsular contracture, luxatio erecta humeri, and AC. However, the thickness varies from the measured angle. To reduce this measurement error, we devised a new morphological parameter, called the anterior band of inferior glenohumeral ligament area (aIGHLA). Methods. The aIGHL samples were collected from 54 patients with AC and from 50 control subjects who underwent shoulder magnetic resonance imaging (MRI) without any evidence of AC. Coronal T2-weighted MRI images were obtained at the shoulder level from each patient. We measured the aIGHLA and aIGHLT at the maximal view of the IGHL in the coronal plane using our picture archiving and communication system. The aIGHLA was measured at the whole cross-sectional area of the IGHL in the most hypertrophied segment of the coronal MR images. The aIGHLT was measured at the thickest point of the IGHL. Results. The average aIGHLA was 55.58 ± 14.16 mm2 in the control group and 83.71 ± 28.45 mm2 in the AC group. The average aIGHLT was 3.47 ± 0.99 mm in the control group and 4.52 ± 1.02 mm in the AC group. AC patients showed significantly greater aIGHLA (p<0.001) and aIGHLT (p<0.001) than control subjects. Receiver operating characteristic (ROC) curve analysis showed that the optimal cut-off score of the aIGHLA was 63.37 mm2, with 79.6% sensitivity, 80.0% specificity, and AUC of 0.84 (95% CI, 0.76–0.92). The optimal cut-off point of the IGHLT was 3.81 mm, with 74.1% sensitivity, 74.0% specificity, and AUC of 0.77 (95% CI, 0.68–0.86). Conclusions. Although the aIGHLA and aIGHLT were both significantly associated with AC, the aIGHLA was a more sensitive diagnostic parameter.